Antigen-specific inhibition of CD4(+) T-cell responses to β-lactoglobulin by its single amino acid-substituted mutant form through T-cell receptor antagonism - Totsuka, Mamoru (Kluwer Academic Publishers, 1997)
T cell responses can be antagonized by some single amino acid-substituted analogs of a peptide ligand for T-cell receptors (TCR), and these are called TCR antagonists. In this study, we addressed the question of whether TCR antagonism can be elicited by a whole protein antigen carrying a mutated T-cell determinant region corresponding to a TCR antagonist peptide. To clarify this, we examined the ability of a single amino acid-substituted mutant form of bovine β-lactoglobulin (β-Lg) to inhibit three CD4(+) T-cell clones recognizing a peptide corresponding to an immunodominant determinant region 119-133 of β-Lg (p119-133). First, we identified pD129A, an analog of p119-133 with a substitution of Ala for (129)Asp, as an antagonist which can inhibit the response of two of the three T-cell clones. Then, using a yeast expression system, we prepared a mutant β-Lg (mutD129A) with the same substitution of Ala for (129)Asp as that in pD129A. This mutant protein could inhibit the proliferation of the two T-cell clones in a manner similar to the effect of pD129A. From these results we can demonstrate that TCR antagonism can be elicited by peptides naturally processed from a single-substituted mutant protein as well as by the corresponding peptides added exogenously.